DESIGNING THE UI/UX OF A MOBILE-BASED ULOS E- COMMERCE APPLICATION TO IMPROVE ACCESSIBILITY AND SALES USING THE UCD METHOD - Holfes Rivaldi Sitanggang; Heni Wulandari; Hermansyah (Bahasa Indonesia, 2026)
Ulos has high cultural and economic value, but its market accessibility in the digital era is still limited due to the dominance of conventional sales. The Yusnita Tenun Uwis Nipes SME in Binjai City faces obstacles in online marketing and a lack of specialized platforms that provide accurate product information. This study aims to design the user interface (UI) and user experience (UX) of a mobile-based ulos e-commerce application to expand market reach and increase sales conversion. Using a User-Centered Design (UCD) approach, this study ensures that the application is designed according to user needs and preferences to be more intuitive and user-friendly. The results of this design are expected to increase product visibility, facilitate digital transactions, and support the preservation of Ulos culture through adaptive technology.